ANALISIS PERILAKU KEAGAMAAN MAHASISWA UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Nurzannah Nurzannah (Hijri, 2017)
The purpose of this study is to determine the religious behavior of students of Faculty of Social and Political Sciences UMSU Semester VI TA. 2016/2017. This research is qualitative research, with approach of Social and Religious Psychology, Technique of collecting data used is questionnaire, observation and interview. Result of research indicate that student behavior of Fisip UMSU Semester VI of academic year 2016-2017 in Medium or Enough category.